PENGARUH GOOD CORPORATE GOVERNANCE, MEKANISME BONUS DAN TUNNGELING INCENTIVE TERHADAP PRAKTIK TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN PERIODE 2020-2023 - Damayanti, Alvia; Richmayati, Maya; Laili, Nur Isra; Ramadhany, Andi Auliya; Fadlilah, Andi Hidayatul (JURNAL AKUNTANSI BARELANG, 2025)
From 2020 to 2023, this research looks at food and drink manufacturing businesses listed on the Indonesia Stock Exchange to see how transfer pricing is affected by good corporate governance, bonus mechanisms, and tunneling incentives. Purposive sampling was used to choose data from consolidation financial reports, which were then analyzed using multiple linear regression. According to the results, Good Corporate Governance considerably decreases Transfer Pricing, suggesting that executive discretion is limited by independent supervisory scrutiny. It seems that performance-based incentives are not the main factor driving Transfer Pricing, since Bonus Mechanisms have a positive but negligible influence. At the same time, Tunneling Incentives) cut down on Transfer Pricing, which means that more oversight and less such tactics are possible with more foreign ownership. The analyzed variables good corporate governance, bonus mechanism and tunneling incentive all show significant correlations with Transfer Pricing, according to the correlation analysis. With an Adjusted R Squared value of 0.266, the model suggests that the variables under investigation account for 26.6% of the variation in Transfer Pricing, while other, unexplored factors contribute to the remaining 73.4%